Răspuns :
A = L × l
a) l = 8 cm
A = 116 cm
8 × L = 116
L = 116 ÷ 8
L = 14, 5 cm
b) L = 2×l
l × 2l = 112, 5 cm
3l = 112,5
l = 112, 5 ÷ 3
l = 37, 5 cm
L = 2 × 37, 5
L = 75 cm
a) l = 8 cm
A = 116 cm
8 × L = 116
L = 116 ÷ 8
L = 14, 5 cm
b) L = 2×l
l × 2l = 112, 5 cm
3l = 112,5
l = 112, 5 ÷ 3
l = 37, 5 cm
L = 2 × 37, 5
L = 75 cm
A = L × l
a) l = 8 cm
A = 116 cm²
8 × L = 116
L = 116 / 8
L = 14, 5 cm
b) L = 2 × l
l × 2l = 112,5 cm²
3l = 112,5
l = 112,5 / 3
l = 37,5 cm
L = 2 × 37,5
L = 75 cm
Sper că te-am ajutat!
a) l = 8 cm
A = 116 cm²
8 × L = 116
L = 116 / 8
L = 14, 5 cm
b) L = 2 × l
l × 2l = 112,5 cm²
3l = 112,5
l = 112,5 / 3
l = 37,5 cm
L = 2 × 37,5
L = 75 cm
Sper că te-am ajutat!